2021
DOI: 10.1103/physrevd.103.064078
|View full text |Cite
|
Sign up to set email alerts
|

Junction conditions in infinite derivative gravity

Abstract: The junction conditions for the infinite derivative gravity theory R þ RFð□ÞR are derived under the assumption that the conditions can be imposed by avoiding the "ill-defined expressions" in the theory of distributions term by term in infinite summations. We find that the junction conditions of such nonlocal theories are much more restrictive than in local theories, since the conditions comprise an infinite number of equations for the Ricci scalar. These conditions can constrain the geometry far beyond the mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…One can compute numerically the convolution of the exact soliton profile (4.1) with the Gaussian function (4.7), where one can see in figures 2 and 3 that nonlocality (σ = 0) smears the behavior of the local soliton near the kink when σ increases: the soliton width is increased by the smearing effect of nonlocality. This effect is already known for zero-thickness topological defects [51,[74][75][76][77][78][79]. Far from the wall, the nonlocal soliton smoothly recovers the asymptotic behavior of the local one.…”
Section: One Introduces the Normalized Gaussian Functionsupporting
confidence: 60%
See 1 more Smart Citation
“…One can compute numerically the convolution of the exact soliton profile (4.1) with the Gaussian function (4.7), where one can see in figures 2 and 3 that nonlocality (σ = 0) smears the behavior of the local soliton near the kink when σ increases: the soliton width is increased by the smearing effect of nonlocality. This effect is already known for zero-thickness topological defects [51,[74][75][76][77][78][79]. Far from the wall, the nonlocal soliton smoothly recovers the asymptotic behavior of the local one.…”
Section: One Introduces the Normalized Gaussian Functionsupporting
confidence: 60%
“…In context to gravity theories, i.e. string-inspired nonlocal extensions of the Einstein gravity, it has been shown that one can get rid of classical singularities, such as black hole singularities [19,24,[57][58][59][60][61][62][63][64][65][66], cosmological singularities [67][68][69][70][71][72][73], and topological defects [74][75][76][77][78][79][80].…”
Section: Introductionmentioning
confidence: 99%
“…This type of transcendental operators with some entire function γ(− ) have been intensely studied in the past years not only in the context of quantum field theories in flat space [29-32, 36, 37], but also to formulate ghost-free infinite-derivative theories of gravity [29,[38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Jhep11(2022)104mentioning
confidence: 99%